THE IMPACT OF SERVICE DIGITALIZATION, SERVICE QUALITY, AND OPERATIONAL EFFICIENCY ON STUDENT SATISFACTION IN USING CAMPUS FACILITIES - Cut Fadilah; Juliana Nasution; Rahmi Syahriza (Nurul Jadid University, 2025)
The development of digital technology has transformed the landscape of higher education institutions, demanding adaptation in the provision of services to students. UINSU, the State Islamic University of North Sumatra, has strived to improve the quality of campus services through digitalization, improved service quality, and operational efficiency. This study analyzes the influence of service digitalization, service quality, and operational efficiency on student satisfaction in using campus facilities at the State Islamic University of North Sumatra (UINSU). Using an associative quantitative method with 100 active UINSU student respondents, this study found that service digitalization and student happiness were positively and significantly influenced by service quality. Improved ease of access to information, speed of administrative processes, and the quality of interactions and physical facilities contributed to positive student experiences. However, operational efficiency showed a negative and significant influence on student satisfaction, indicating a dissonance between campus efficiency efforts and student perceptions and comfort. These findings emphasize the importance of UINSU balancing efficiency with student needs and expectations to ensure an optimal learning experience.